1954
DOI: 10.1084/jem.99.3.227
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Influenza Virus Multiplication by N-Glycosides of Benzimidazoles

Abstract: Chloro derivatives of benzimidazole were found to be 2 to 3 times more active than corresponding methyl derivatives in causing inhibition of Lee virus multiplication in chorioallantoic membrane cultures in vitro. The most active benzimidazole derivative thus far tested is 5,6-dichloro-1-ß-D-ribofuranosylbenzimidazole (DRB); it caused 75 per cent inhibition of Lee virus multiplication in membrane cultures at a concentration of 0.38 x 10–4 M. On the other hand, 5,6-dimethyl-1-alpha;-D-ribofuranosylbenzimidazole,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
80
0

Year Published

1956
1956
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(82 citation statements)
references
References 30 publications
2
80
0
Order By: Relevance
“…It was found that 5,6-dichloro-1-␤-D-ribofuranosylbenzimidazole (DRB), which inhibits mRNA elongation, blocked influenza virus multiplication (28). Recent research showed that DRB did not affect viral primary transcription, while ␣-amanitin, which inhibits both mRNA initiation and elongation, totally blocked the viral transcription and replication.…”
mentioning
confidence: 99%
“…It was found that 5,6-dichloro-1-␤-D-ribofuranosylbenzimidazole (DRB), which inhibits mRNA elongation, blocked influenza virus multiplication (28). Recent research showed that DRB did not affect viral primary transcription, while ␣-amanitin, which inhibits both mRNA initiation and elongation, totally blocked the viral transcription and replication.…”
mentioning
confidence: 99%
“…DRB is a halogenated adenosine analog which was introduced more than 30 years ago as a potential antiviral agent with effect on influenza, polio, and other viruses [Tamm et al, 1954;Tamm and Nemes, 19571. However, it was soon found that DRB had a profound effect on host cell functions and DRB instead has become a useful tool in cell biology research.…”
Section: Discussionmentioning
confidence: 99%
“…N -alkoxy- and N -hydroxy-benzimidazoles have been shown to exhibit a number of biological activities such as, acting as a growth inhibitor of Lactobacillus leichmanii 1 and influenza virus, 2 inhibition of bacterial transcriptase factors, 3 and anti-HIV-1 activity. 4 Only two general methods for the preparation of N -alkoxybenzimidazoles can be found in the literature.…”
Section: Introductionmentioning
confidence: 99%